(untitled) (Global Journal of Human-Social Science, 2017)
The online newspaper is increasingly taking the place of the hardcopy newspaper As readers switch to popular online newspapers it behoves the internet-based medium to live up to and better play the very important function to the society carried out by the hardcopy newspapers But the increasing cases of fake news in the blogosphere seem likely to detract from the credibility which many place on popular online newspapers When readers apply the Uses and Gratifications as well as the Selectivity Factors theories this will go a long way in whittling down the influential role of the press in the society Using the survey research design this researcher set out to explore the influence which the circulation of fake news has on the perception members of the public have of Nigeria s online newspapers Drawing the sample size from Enugu metropolis it was found that while the prevalence of fake news in Nigeria is high popular online newspapers do not play much role in the dissemination of fake news It was also discovered that most Nigerians see reports on popular online news platforms as credible and that there is difference between information on online newspapers and those circulated through social media